PENGGUNAAN MEDIA INTERAKTIF "TANTANGAN MYSTERY BOX” PADA LITERASI NUMERASI KELAS 1 MADRASAH IBTIDAIYAH” - Salsabila, Anisa; Sasabilla, Devi; Hafidz, Alifandi; Fakiroh, Dzakiyatul; Oktaviani, Rizka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Literacy and numeracy learning in grade 1 children is very important to develop their basic skills. The purpose of this study was to explain the use of the Mystery Box Challenge media on the early numeracy literacy skills of grade 1 students at MI Haji Hasyim, describe the numeracy literacy skills after using the Mystery Box Challenge media, and describe the problems that arise when teachers use the Mystery Box Challenge media. In this study, data were collected through interviews, observations, and documentation using a qualitative approach. The Miles and Huberman model is the reference framework in data analysis to produce accurate, relevant, and descriptive conclusions. This study revealed several important findings related to the learning process in mathematics learning when using mystery box media on numeracy literacy skills which went very well, numeracy literacy skills after using mystery box media were 20 students who reached levels 1-4 while 4 students still reached levels 1-2, and the obstacles experienced were the learning time which took quite a long time and numeracy literacy learning at the previous level of education was less than optimal.